Analisis Persaingan Harga Di Pasar Tradisional Dalam Etika Bisnis Islam: Studi Kasus Pasar Tradisional Kelurahan Muara Sabak Ulu - Juminem Sri Lestari; Titin Agustin Nengsih; Muhamad Subhan (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Business is an activity of the economy, where business activities take place in the market. Where the market is a meeting place for traders and buyers. One of them is the Muara Sabak Ulu Traditional Market with traders who are predominantly Muslim. Competition is an organization or individual vying to get what they want. This study uses a type of qualitative research and the object of this research is the traditional market traders of Muara Sabak Ulu. Sources of data used are primary data and secondary data, the techniques used in collecting data are observation, interviews and documentation. The determination of the pricing mechanism at the Muara Sabak Ulu Traditional Market is found in the selling price and the interest of the buyer where the trader will raise the price of the goods above the price given by the distributor. The factor for the occurrence of violations of business ethics in the Muara Sabak Ulu Traditional Market is because the opportunity to cheat will encourage people to do so. The intention to cheat will increase if the trader is under pressure to achieve a goal that he feels is very important. There are traders in the Muara Sabak Ulu Traditional Market who comply with the ethics of trading and the principles of Islamic business ethics and there are also those who are not in accordance with the principles of Islamic business ethics.